Aesthetic Badi in Nazamim systems Industrial products (Journal of the College of Basic Education, 2022)
This research is concerned with studying the importance of employing the arts of Arabic rhetoric in the design processthen a language capable of generating meanings; Which affects the user's reactions to it and its interpretationIt has many meanings and connotations that this interpreter gives and generated from the textdesign of the industrial product itself. The first chapter dealt with the research problem, which was manifested in the questionNext: What is the extent of the constructive interrelationship between the beautiful, which is a linguistic art, and its employment inindustrial product designs?He discussed the wonderful research and its divisions as being one of the arts of Arabic rhetoric and explaining its aesthetic inDesign systems w down to a set of results that showed aesthetic improvementsmoral and that translated into function design;